Geospatial mapping to estimate timely access to surgical care in nine low-income and middle-income countries. (27th April 2015) - Raykar, Nakul P; Bowder, Alexis N; Liu, Charles; Vega, Martha; Kim, Jong H; Boye, Gloria; Greenberg, Sarah L M; Riesel, Johanna N; Gillies, Rowan D; Meara, John G; Roy, Nobhojit
Abstract: Background: The Lancet Commission on Global Surgery calls for universal access to safe, affordable, and timely surgical care. Two requisite components of timely access are (1) the ability to reach a surgical provider in a given timeframe, and (2) the ability to receive appropriately prompt care from that provider. We chose a threshold of 2 h in view of its relevance in time-to-death in post-partum haemorrhage. Here, we use geospatial mapping to enumerate the percentage of a nation's population living within 2 h of a surgeon and the surgeon-to-population ratio for each provider. Methods: Geospatial mapping was used to identify the population living within a 2-h driving distance (access zone) of a health-care facility staffed by a surgeon. Surgeon locations were extracted from Ministries of Health, professional society databases, and published literature for countries which had available data. Data were reviewed by individuals knowledgeable of in-country distribution. Spatial distribution of providers was mapped with Google Maps engine. Access zones were constructed around every provider through estimation of driving times in Google Maps. The number of people living within zones was estimated with the Socioeconomic Data and Applications Center Population Estimation Service. Surgeon-to-population ratios were constructed for every individual access zone and averaged to report a single ratio. Findings: Results (% country's population living within an access zone; average surgeon:population ratio within all access zones) are reported for nine countries with available data: Somaliland (16·9%; 1:118 306), Botswana (31·0%; 1:64 635), Ethiopia (39·6%; 1:229 696), Rwanda (41·3%; 1:158 484), Namibia (43·4%; 1:69 385), Zimbabwe (54%; 1:148 292), Mongolia (55·5%; 1:10 500), Sierra Leone (70·3%; 1:106 742), and Pakistan (84·4%, 1:139 299). Surgeon-to-population ratios vary substantially even within countries; in Sierra Leone, urban access zones have a ratio of 1:45 058 and rural access zones have a ratio of 1:467 929. Interpretation: Surgical access is poor in many low-income and middle-income countries, even when using a narrow definition of surgical access consisting only of timeliness. Living outside of an access zone makes timely access to surgical care highly unlikely, and in view of low surgeon-to-population ratios and poor prehospital transport, even living within a 2-h access zone might not confer 2-h access. Investments in infrastructure and training must be prioritised to address widespread disparity in access to timely surgery. Funding: None.